Comparison of Effect of Two Induction Doses of Methohexitone on Infants Delivered by Elective Caesarean Section. Issue 5917 (1st June 1974) - Holdcroft, Anita; Robinson, M. J.; Gordon, H.; Whitwam, J. G.
Abstract : Observations were made on 26 infants delivered by elective caesarean section under general anaesthesia. A standard anaesthetic technique was employed using a methohexitone, relaxant, nitrous oxide-oxygen sequence with regulated ventilation and the administration of papaveretum after clamping the umbilical cord. In 12 patients the induction dose of methohexitone was 1·4mg/kg and in 14 it was reduced to 1·0 mg/kg. There were no significant differences between the two groups in the clinical status of the mothers, in operative technique and timing, or in the value of PO2, PCO2, and pH in the umbilical cord venous blood. The infants whose mothers received the lower dose of methohexitone were in better condition, as assessed by the number needing assisted ventilation, the time taken to establish regular respiration, the Apgar score, and the "Apgar minus colour" score.